An evaluation of inter and intra population structure of Uttar Pradesh, inferred from 24 autosomal STRs - Ikramul Haque; Shivani Dixit; Akash Kumar; Akshay Kumar; Sunita Verma; Devinder Kumar; Ankit Srivastava; R. K. Kumawat; Divya Shrivastava; Gyaneshwer Chaubey; Pankaj Shrivastava (Taylor & Francis Group, 2022)
Aim The present study was designed to explore the STR diversity and genomic history of the inhabitants of the most populous subdivision of the country. A set of 24 hypervariable autosomal STRs was used to estimate the genetic diversity within the studied population. A panel of 15 autosomal STRs, which is most common in the previously reported data sets, was used to estimate the genetic diversity between the studied population, and obtained unique relations were reported here. Method The genetic diversity and polymorphism among 636 individuals of different ethnic groups, residing in Bareilly, Pilibhit, Shahjahanpur, Gorakhpur, Jhansi, and Varanasi regions of Uttar Pradesh, India, was investigated. This investigation was carried out via 24 autosomal STRs. Result The 24 loci studied showed the highest value of combined power of discrimination (CPD = 1), combined power of exclusion (CPE = 0.99999999985), combined paternity index (CPI = 6.10 × 109) and lowest combined matching probability (CPM = 7.90 × 10−31). Conclusion The studied population showed genetic closeness with the population of Uttarakhand, the Jats of Delhi,the Jat Sikh (Punjab), and the population of Rajasthan. Among the tested loci, SE33 and Penta E were found to be most useful in terms of the highest discrimination power, lowest matching probability, the highest power of exclusion, and highest polymorphism information content for the Uttar Pradesh population .